New Aspects of Kidney Fibrosis–From Mechanisms of Injury to Modulation of Disease - Moeller, Marcus J.; Kramann, Rafael; Lammers, Twan; Hoppe, Bernd; Latz, Eicke; Ludwig-Portugall, Isis; Boor, Peter; Floege, Jürgen; Kurts, Christian; Weiskirchen, Ralf; Ostendorf, Tammo (Frontiers in Medicine, 2022)
Organ fibrogenesis is characterized by a common pathophysiological final pathway independent of the underlying progressive disease of the respective organ. This makes it particularly suitable as a therapeutic target. The Transregional Collaborative Research Center “Organ Fibrosis: From Mechanisms of Injury to Modulation of Disease” (referred to as SFB/TRR57), funded by the German Research Foundation (DFG) and hosted by the medical faculties of RWTH Aachen University and the University of Bonn, has in the past 12 years (2009-2021) specifically dedicated a lot of attention to this topic. The research focus of the SFB/TRR57 consortium was on organ fibrosis in the liver and kidneys with the ultimate goal of discovering new common but also distinct pathways. Moreover, the consortium identified new mechanisms and established novel therapeutic approaches to interfere with hepatic and renal fibrosis. This review covers the consortium's key kidney-related findings. The liver-related research findings are summarized in a second article, which also appears in Frontiers in Medicine. Within the consortium, we addressed three overarching questions: (i) What are the relevant mechanisms and signaling pathways triggering renal fibrosis?, (ii) What are the immunological mechanisms, cells and molecules that contribute to renal fibrosis? (iii) How can renal fibrosis be modulated? Here, we highlight the role of specific fibroblast and pericyte subtypes as myofibroblast precursors and discuss new immune-mediated mechanisms in the initiation, progression and limitation of fibrosis development with a focus on the activation of inflammasomes in various kidney diseases. We report on the role of activated glomerular parietal epithelial cells and growth factors in the development of glomerulosclerosis and tubulointerstitial fibrosis. Finally, we describe efforts towards the development of novel biomarkers and non-invasive imaging techniques for staging and treatment monitoring in kidney fibrosis, aiming to foster the translation of basic science into clinic practice.